Sistem Informasi Pengelolaan Keuangan Dana Desa Dengan Metode Accrual Basic Pada Kelurahan Kutoharjo Kecamatan Kaliwungu - Kamto Sudibyo, sukemi; Safitri , Ana; Siswanto, eko (Jurnal Ilmiah Sistem Informasi, 2023)
Every government agency or company must have a different financial plan, currently all government agencies or companies are required to make reports relating to their financial developments. This information is compiled and presented by the village government in the form of balance sheets, journal reports, because financial reports are a form of accountability from the Village Head or the Village Treasurer. one by one. The results of this study are to make it easier for the Kutoharjo Village Office in the process of financial management, assisting in the process of inputting financial data on an accual basis when giving or receiving cash, before a cash transaction occurs which acknowledges the effect of the transaction regardless of when cash is received or paid, data search, and village fund financial reports by optimizing data security.